Variations in Nutritional Requirements Across Bee Species - Barraud, Alexandre; Barascou, Lena; Lefebvre, Victor; Sene, Deborah; Le Conte, Yves; Alaux, Cedric; Grillenzoni, Francesca-Vittoria; Corvucci, Francesca; Serra, Giorgia; Costa, Cecilia; Vanderplanck, Maryse; Michez, Denis (Frontiers in Sustainable Food Systems, 2022)
With 2,000 species currently recorded in Europe, bees are a highly diversified and efficient group of pollinating insects. They obtain their nutrients from nectar and pollen of flowers. However, the chemical composition of these resources, especially of pollen (e.g., protein, lipid, amino acids, fatty acids, or sterol content), is highly variable among plant species. While it is well-known that bees show interspecific variation in their floral choices, there is a lack of information on the nutritional requirements of different bee species. We therefore developed original experiments in laboratory conditions to evaluate the interspecific variations in bee nutritional requirements. We analyzed the chemical content of eight pollen blends, different in terms of protein, lipid, amino acids, and sterols total concentration and profiles. Each pollen blend was provided to four different bee model species: honey bees (Apis mellifera), bumblebees (Bombus terrestris), mason bees (Osmia bicornis and Osmia cornuta). For each species, specific protocols were used to monitor their development (e.g., weight, timing, survival) and resource collection. Overall, we found that the nutritional requirements across those species are different, and that a low-quality diet for one species is not necessarily low-quality for another one. While honey bees are negatively impacted by diets with a high protein content (~40%), bumblebees and mason bees develop normally on these diets but struggle on diets with a low total amino acid and sterol content, specifically with low concentrations of 24-methylenecholesterol and β-sitosterol. Overall, our study supports the need of conserving and/or introducing plant diversity into managed ecosystems to meet the natural nutritional preferences of bees at species and community level.